2021
DOI: 10.3390/separations8090137
|View full text |Cite
|
Sign up to set email alerts
|

Development of Green and Efficient Extraction Methods of Quercetin from Red Onion Scales Wastes Using Factorial Design for Method Optimization: A Comparative Study

Abstract: Waste resulting from edible plants is considered one of the best sources of valuable phytochemicals. A promising approach for using these appreciated wastes is extracting precious medically important constituents, for example, free quercetin. Two new cost-effective and green extraction methods are introduced in the present study: ultrasound-assisted glycerol extraction (UAGE) and microwave-assisted extraction (MAE). These extraction protocols are optimized using factorial design to define the highest yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…Test tablets are considered bioequivalent to Dostinex tablets and could be approved as a good substitute for the generic product. Estimation for the greenness of the proposed LC/MS/MS method AGREE approach is simple and reliable for the assessment of eco-friendly characters of the analytical method [19,21,[36][37][38][39][40][41][42][43]. The final greenness numerical value was 0.63 with a relatively pale green color inside the pictogram as demonstrated in Additional file 1: Fig.…”
Section: Results Of Pharmacokinetic Parametersmentioning
confidence: 95%
See 1 more Smart Citation
“…Test tablets are considered bioequivalent to Dostinex tablets and could be approved as a good substitute for the generic product. Estimation for the greenness of the proposed LC/MS/MS method AGREE approach is simple and reliable for the assessment of eco-friendly characters of the analytical method [19,21,[36][37][38][39][40][41][42][43]. The final greenness numerical value was 0.63 with a relatively pale green color inside the pictogram as demonstrated in Additional file 1: Fig.…”
Section: Results Of Pharmacokinetic Parametersmentioning
confidence: 95%
“…AGREE approach is simple and reliable for the assessment of eco-friendly characters of the analytical method [ 19 , 21 , 36 43 ]. The final greenness numerical value was 0.63 with a relatively pale green color inside the pictogram as demonstrated in Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This level is particularly high, considering that other studies have reported yields in quercetin usually varying from 5.32 (Imeneo et al., 2022) to 17.32 mg g −1 DM (Kim et al., 2019). On the other hand, a quercetin yield as high as almost 27 mg g −1 DM has been attained using a methodology based on microwave‐assisted extraction and hydroethanolic solvent (Abd‐Elsalam et al., 2021). However, in none of these studies it was mentioned quercetin liberation from its glycoconjugates.…”
Section: Resultsmentioning
confidence: 99%
“…High performance liquid chromatography (HPLC) is one of the most frequently used techniques for the determination of drugs, [1][2][3][4][5][6][7][8] natural products, [9][10][11][12][13] foods, [14][15][16][17][18] and important environmental markers. [19][20][21][22][23][24] Quality control analysis is a vital step to ensure correct dosage during production, but the routine analysis for each pharmaceutical formulation alone results in a large amount of hazardous chemical waste.…”
Section: Introductionmentioning
confidence: 99%